2022
DOI: 10.3390/jcm11030656
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Multimorbidity and Quality of Life in a Primary Care Setting: The Mediating Role of Dyspnea

Abstract: Multimorbidity is known to impair Quality of Life (QoL) in patients in a primary setting. Poor QoL is associated with higher dyspnea perception. How multimorbidity and dyspnea perception are related to QoL needs clarification. The aim of the present study is to evaluate the mediating role of dyspnea perception in the relationship between multimorbidity and QoL in adults with and without airflow obstruction in a primary care setting. Seventeen general practitioners participated in the study: a total of 912 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…One plausible explanation is that multimorbidity may increase severity and distress ratings by increasing overall symptom burden 69 and emotional distress 70 and decreasing functional status 71 and quality of life. 72 This hypothesis is consistent with our current findings across the three LPAs, that patients with the worse profiles reported lower KPS scores, higher levels of depressive symptoms and anxiety, and higher levels of other common symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…One plausible explanation is that multimorbidity may increase severity and distress ratings by increasing overall symptom burden 69 and emotional distress 70 and decreasing functional status 71 and quality of life. 72 This hypothesis is consistent with our current findings across the three LPAs, that patients with the worse profiles reported lower KPS scores, higher levels of depressive symptoms and anxiety, and higher levels of other common symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…As it can cause signi cant clinical symptoms (such as cough, phlegm, or hemoptysis), result in poor quality of life, and increased economic burden and mortality rates, it has become an important public health problem [8,9]. Studies have reported that psychological comorbidities are more common in patients with chronic airway disease than the general population [10]. Bronchiectasis, as a kind of chronic airway diseases, also commonly coexists with psychological comorbidities, such as anxiety and depression [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the 6-min walking distance (6MWD) has been found to be a valuable tool for evaluating the functional status and mortality risk of CRD patients due to its ease of use, cost-effectiveness, and high potential for standardization [6]. Similarly, the modified Medical Research Council (mMRC) questionnaire and the COPD assessment test (CAT) have been effectively used in clinical guidelines and, consequently, in clinical practice for staging disease severity and predicting health status deterioration, exacerbations, and mortality, not only in COPD but also in other clinical settings [15]. Combining many of the aforementioned clinical and functional measures, the BODE index has progressively emerged as a composite clinical marker, with high prognostic value compared to other standard geriatric tools [16].…”
mentioning
confidence: 99%